2015
DOI: 10.1021/jacs.5b05992
|View full text |Cite
|
Sign up to set email alerts
|

Intermediates Involved in the 2e/2H+ Reduction of CO2 to CO by Iron(0) Porphyrin

Abstract: The reduction of CO2 by an iron porphyrin complex with a hydrogen bonding distal pocket involves at least two intermediates. The resonance Raman data of intermediate I, which could only be stabilized at -95 °C, indicates that it is a Fe(II)-CO2(2-) adduct and is followed by an another intermediate II at -80 °C where the bound CO2 in intermediate I is protonated to form a Fe(II)-COOH species. While the initial protonation can be achieved using weak proton sources like MeOH and PhOH, the facile heterolytic cleav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
156
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(167 citation statements)
references
References 33 publications
11
156
0
Order By: Relevance
“…Similar studies can be found in the literature in which the effects of different enzyme types having different metal active centers and the contribution of those metals to the formation of CO and formate were investigated 76, 77. Nørskov and co‐workers reported a good overiew of the design parameters for enzymatic catalysts using DFT calculations.…”
Section: Homogeneous Electrocatalysis For Co2 Reductionsupporting
confidence: 67%
See 1 more Smart Citation
“…Similar studies can be found in the literature in which the effects of different enzyme types having different metal active centers and the contribution of those metals to the formation of CO and formate were investigated 76, 77. Nørskov and co‐workers reported a good overiew of the design parameters for enzymatic catalysts using DFT calculations.…”
Section: Homogeneous Electrocatalysis For Co2 Reductionsupporting
confidence: 67%
“…Although various molecular catalysts (porphyrins, corroles, cyclams, naphthyridines, and so forth) with metal centers such as Pd, Ru, Fe, Co, and Ni were investigated,31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49 in the years after the discovery of Lehn's catalyst, most research has been focused on Re‐containing complexes. With an estimated average concentration of 1 ppb, Re, together with other noble metals, is one of the rarest elements in Earth's crust.…”
Section: Homogeneous Electrocatalysis For Co2 Reductionmentioning
confidence: 99%
“…The cyclic voltammogram (CV) of 1 ‐Cl was first measured in 0.1 M Bu 4 N(PF 6 ) acetonitrile solution under argon using a glassy carbon (GC) electrode. CV of 1 ‐Cl displayed three quasi‐reversible redox waves at −0.73, −1.61, and −1.90 V versus ferrocene (Figure a, all potentials reported in this work are referenced to ferrocene), which could be assigned to the formal Fe III/II , Fe II/I , and Fe I/0 couples, respectively . A linear correlation between the peak current and the square root of scan rate was observed (Figure b), indicating the free diffusing of 1 ‐Cl under non‐catalytic conditions.…”
Section: Figurementioning
confidence: 72%
“…Fe porphyrins have received considerable attention among these catalysts . They show high activity and stability for the selective CO 2 ‐to‐CO conversion, and they provide an ideal platform to investigate various structural effects on CO 2 RR, because the meso ‐substituents of the porphyrin ring can be systematically modified to introduce different acid/base groups and positively/negatively charged moieties .…”
Section: Figurementioning
confidence: 99%
“…The receptor properties around the low-valent metal center are further assisted by additional hydrogen bonding motifs to stabilize the CO 2 substrate adduct formed. Unfortunately, triggering of the observed enzyme-like redox activity still requires short-wavelenght UV-light leading to catalyst stability problems, and the activity of the catalytic Fe-center may also be hampered by self-inibition with the reaction product carbon monoxide [172]. In general, selective CO 2 reduction systems utilizing a significant share of visible light in the absence of any additional photosensitizer are currently still very rare [173][174][175] and usually contain expensive transition metals with limited availability such as rhenium or iridium instead of using earth-abundant raw materials.…”
Section: Photocatalytic Enzyme Models For Co 2 Reductionmentioning
confidence: 99%